1999
DOI: 10.1063/1.124666
|View full text |Cite
|
Sign up to set email alerts
|

GaN homoepitaxial layers grown by metalorganic chemical vapor deposition

Abstract: GaN homoepitaxial layers were grown using metalorganic chemical vapor deposition on the highly conductive GaN bulk crystals grown at high hydrostatic pressure. The epitaxial growth process was monitored by reflectivity of red laser light. The oscillations of its intensity served for the precise evaluation of the growth rate. The layers were then investigated using far-infrared reflectivity (FIR), x-ray diffraction, and photoluminescence. The FIR spectrum gave small free-electron concentration in the layers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 16 publications
1
39
0
Order By: Relevance
“…As observed by other groups [16][17][18], high-resolution PL studies confirmed the high-crystalline quality of our undoped and Si-doped GaN homoepitaxial layers [19]. In particular, the Si-doped homoepitaxial sample exhibits sharper excitonic PL (linewidthsp1 meV) compared to that reported previously for GaN grown on Al 2 O 3 with similar Si doping levels [20].…”
Section: Gan Homoepitaxial Layerssupporting
confidence: 67%
See 1 more Smart Citation
“…As observed by other groups [16][17][18], high-resolution PL studies confirmed the high-crystalline quality of our undoped and Si-doped GaN homoepitaxial layers [19]. In particular, the Si-doped homoepitaxial sample exhibits sharper excitonic PL (linewidthsp1 meV) compared to that reported previously for GaN grown on Al 2 O 3 with similar Si doping levels [20].…”
Section: Gan Homoepitaxial Layerssupporting
confidence: 67%
“…Though not nearly as sharp as the excitonic PL observed from undoped GaN homoepitaxial layers with linewidths of B0.1 meV [16][17][18][19], the bandedge emission from these free-standing (thick) HVPE GaN templates is characterized by linewidths less than 1 meV [14]. An example of a high-resolution PL spectrum obtained at 5 K that demonstrates the high crystallinity of this material is shown in the inset of Fig.…”
Section: Free-standing (Thick) Hvpe Ganmentioning
confidence: 99%
“…These crystals were tested to be semi-insulating with a perfect crystallographic structure. 7 Prior to growth, the ͑0001͒ Ga face, which was found to be the best face polarity for a homoepitaxial layer, 8 as the nitrogen precursor and the group-III element were provided by standard solid-source effusion cells. An unintentionally doped GaN layer of about 1 m was grown at 800°C on a Mg-doped GaN single crystal, followed by a 200-Å-thick AlGaN layer.…”
mentioning
confidence: 99%
“…6,7 This leads to photoluminescence spectra with very well-resolved excitonic transition lines of widths below 1 meV. 8 Recently, Mg-doped high-pressure-grown bulk GaN crystals were shown to be semi-insulating with perfect crystallographic structure.…”
Section: ϫ2mentioning
confidence: 99%